Empiema: [Empyema: An Update Approach] - Helmia Hasan; Devi Ambarwati (Faculty of Medicine Universitas Airlangga, 2018)
Empyema is a collection of exudative fluid in the pleural cavity associated with the occurrence of pulmonary infection. Empyema is often caused by complications of pneumonia but can also be caused by infection from elsewhere. Community-aquired pneumonia has an incidence of 8 to 15 per 1000 per year. Forty to 57% of patients with pneumonia, may develop into a parapneumonic effusion. Approximately 5 to 10% of parapneumonic effusions develop into empyema. All patients with parapneumonia and empyema effusions require antibiotic therapy early and adequate. Sterile pleural effusions with PH ≥ 7,20 were observed and protected by adequate antibiotics. Empyema and localized pleural effusions and parapneumonic effusions with PH <7.20 or glucose <60 mg / dL or the presence of germs on positive examination and culture require drainage. Delays in drainage may increase morbidity and mortality rates. Management of empyema depending on the stage, antibiotics or thoracocentesis, thoracostomy, thoracostomy with fibrinolytic therapy, thoracoscopy, dekortication and open thoracotomy.